Economic impact of cardiac implantable electronic device infections: cost analysis at one year in a large U.S. health insurer. (2nd July 2020) - Eby, Elizabeth L.; Bengtson, Lindsay G. S.; Johnson, Michael P.; Burton, Mark L.; Hinnenthal, Jennifer
Abstract: Aims: Cardiac device infections (CDIs) are serious adverse events associated with morbidity and mortality, significant costs and increased healthcare utilization. The objective of the current study was to characterize the CDI rate by device type, risk factors for infection and healthcare costs from a large U.S. health insurer perspective. Materials and Methods: A retrospective analysis of a large U.S. health insurer database identified commercial and Medicare Advantage with Part D (MAPD) members ≥18 years with ≥1 claim for a cardiac implantable electronic device (CIED) procedure between 01 October 2011 and 31 October 2015. CIEDs included pacemakers (IPG), implantable cardioverter defibrillators (ICDs), and cardiac resynchronization therapy – pacemakers without (CRT-P) and with defibrillation (CRT-D). Probabilities of CDI through one-year post implant were estimated using the Kaplan–Meier method. A regression model with stepwise variable selection was used to select risk factors associated with CDIs. Results: A total of 63, 406 patients were included with an overall CDI rate of 1.28% (1.0% de novo and 1.74% replacement devices), varying by device type: IPG = 0.91%; ICD = 1.63%; CRT- p = 1.50%; CRT- D = 2.22%. The average adjusted annual medical costs were 2.4 times greater [95% confidence interval (CI) = 2.1–2.7] for those with an infection compared to those without, and the incremental cost difference was estimated to be 57, 322 [95% CI 46, 572–70, 484]. Observed risk factors of CDIs included prior device infection [Odds ratio (OR) = 11.356; 95% CI = 7.923–16.276], undergoing a CIED replacement procedure (OR = 1.644; 95% CI = 1.361–1.987), implantation of a high-power device (OR = 1.354; 95% CI = 1.115–1.643), and younger age (age < 65) (OR = 1.607; 95% CI = 1.307–1.976). Conclusions: The CDI rate at one year ranged from 0.91%–2.22% depending on device type. Management of CDIs among commercial and MAPD members is associated with high healthcare expenditures.